Orbital control of noncollinear magnetic order in nickelate heterostructures - Frano, Alex; Haverkort, Maurits W.; Lu, Yi (Arxiv, 2013)
We have used resonant x-ray diffraction to develop a detailed description of antiferromagnetic ordering in epitaxial superlattices based on two-unit-cell thick layers of the strongly correlated metal LaNiO3. We also report reference experiments on thin films of PrNiO3 and NdNiO3. The resulting data indicate a spiral state whose polarization plane can be controlled by adjusting the Ni d-orbital occupation via two independent mechanisms: epitaxial strain and quantum confinement of the valence electrons. The data are discussed in the light of recent theoretical predictions.
Gesehen am 24.11.2017